Geoelectrical parameters for the estimation of hydrogeological properties - M. T., Noorellimia; W., Aimrun; M. M. Z., Azwan; Abdullah, A. F. (Springer, 2019)
Excessive groundwater extraction could cause environmental degradation such as surface water depletion, saltwater intrusion, and many more. Therefore, groundwater should be extracted in sustainable way to avert the harmful consequences. An accurate amount of sustainable groundwater yield can be obtained through the groundwater flow model that has low uncertainty. It is important to incorporate the actual hydrogeological properties into groundwater flow modeling to reduce the uncertainty. The purpose of this study is to estimate hydrogeological properties, namely, hydraulic conductivity (K) and transmissivity (T), by combining the electrical resistivity (ER) and induced polarization (IP) methods into an analytical equation. This study used an analytical equation that relates the geoelectrical parameters to the hydrogeological properties. The ER and IP methods were applied to improve the accuracy of geoelectrical parameters using the ABEM Lund Imaging system. The developed analytical equation was compared with other studies for verification. The results showed that the analytical equation model developed in this study had the lowest error compared to that of other published analytical equation models. Therefore, the combination of the ER and IP methods with a new proposed constant value for the analytical equation increased the accuracy of hydrogeological properties.